Metabolic Fingerprinting by 1HNMR for Discrimination of the Two Species Used as Radix Bupleuri - Qin, Xuemei; Dai, Yuntao; Liu, Ning Qing; Li, Zhenyu; Liu, Xiaojie; Hu, Jie; Choi, Young Hae; Verpoorte, Robert (Planta Medica, 2012)
Radix Bupleuri is a traditional Chinese medicine harvested from two Bupleurum species (B. chinense and B. scorzonerifolium). It is widely used and is sourced from different regions of China. 1H NMR spectroscopy and multivariate data analysis were applied to 67 Radix Bupleuri samples to discriminate the two species, and explore the influences of habitat and culture method on the quality of Radix Bupleuri based on their metabolomics profiles. Metabolites responsible for the differences between the two species were higher levels of arginine, citric acid, sucrose, saikosaponin b1/b2 analogs, volatile oil with an (E)-2-olefin aldehyde fragment, and fatty acids in B. scoreonerifolium, and more saikosaponin a/c/d analogs in B. chinense. The variances of two cultivation areas were observed due to the higher amount of saikosaponins a/c/d in samples from Shaanxi and lipidsin samples from Shanxi. No obvious difference was detected between cultivars and wild type. 1HNMR metabolomics can simultaneously detect saikosaponins and hydrocarbon aldehydes, and also differentiate the two main saikosaponin skeletons, making it a suitable tool for the species discrimination and quality evaluation of Radix Bupleuri.
Keywords: metabolomics; 1H-NMR; Apiaceae; Radix Bupleuri; Bupleurum chinense; Bupleurum scorzonerifolium; saikosaponins; quality control